PENINDAKAN HUKUM TERHADAP PELANGGAN DAN PEKERJA SEKS KOMERSIAL - Selvidiyanti Harefa; Suriani Suriani; Ismail Ismail (Lembaga Penelitian dan Pengabdian kepada Masyarakat (LPPM) Universitas Darma Agung, 2020)
Prostitution is a fundamental structural problem that occurs in society because it is still understood as a moral problem. Provisions related to prostitution are regulated in the Criminal Code (KUHP), namely Article 296 and Article 506. It can be seen that criminal law only categorizes prostitution as a criminal act against its intermediaries (Pimp or Pimp). Whereas in cracking down on Customers and Commercial Sex Workers not in the Criminal Code specifically regulate it, a legal vacuum occurs. In this paper using a normative research method with the problem approach is the statutory approach. The problem raised in this paper is how the categories of perpetrators in commercial sex activities and how legal action in dealing with customers and commercial sex workers. Based on this, it can be concluded that the regulations governing law enforcement against customers and commercial sex workers are regulated based on the respective regional regulations in each region.